KONTRIBUSI POWER OTOT TUNGKAI, FLEKSIBILITAS, PANJANG TUNGKAI, DAN BERAT BADAN TERHADAP DAYA TAHAN TENDANGAN DOLLYO CHAGI ATLET TAEKWONDO JUNIOR PADA CLUB SATYA VICTORY - Nabawiah, Uswatun; Surisman; Suwarli; Nurseto, Fransiskus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how much contribution of leg muscle power, flexibility, leg length, and weight to the endurance of dollyo chagi kicks of junior taekwondo athletes at the Satya Victory club. The research method used is correlational research with sampling using total sampling. The research subjects used were athletes who actively train at the Satya Victory club, aged 10-15 years and actively training for at least 1 year, totaling 40 people. The research instrument used to obtain data on leg muscle power used a standing board jump test, flexibility with a sit and reach test, leg length with an anthropometer, body index using a scale and dollyo chagi kicks using a dollyo chagi kick test. The results of the study showed that 1) the contribution of leg muscle power to the endurance of dollyo chagi kicks of junior taekwondo athletes at the Satya Victory club was 25.1%. 2) the contribution of flexibility to the endurance of dollyo chagi kicks of junior taekwondo athletes at the Satya Victory club was 22.9%. 3) The contribution of leg length to the endurance of the dollyo chagi kick of junior taekwondo athletes at the Satya Victory club was 12.6%. 4) The contribution of weight to the endurance of the dollyo chagi kick of junior taekwondo athletes at the Satya Victory club was 9.8%. Simultaneously, the four variables contributed 29.4%, while the remaining 70.6% was influenced by other factors not examined in this study.